2021
DOI: 10.1007/s10483-021-2750-8
|View full text |Cite
|
Sign up to set email alerts
|

On well-posedness of two-phase nonlocal integral models for higher-order refined shear deformation beams

Abstract: Due to the conflict between equilibrium and constitutive requirements, Eringen’s strain-driven nonlocal integral model is not applicable to nanostructures of engineering interest. As an alternative, the stress-driven model has been recently developed. In this paper, for higher-order shear deformation beams, the ill-posed issue (i.e., excessive mandatory boundary conditions (BCs) cannot be met simultaneously) exists not only in strain-driven nonlocal models but also in stress-driven ones. The well-posedness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 32 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Solutions to the relative elastostatic problem can be found in [87]. It is worth noting that the outcomes contributed in [43] amend the erroneous statements in [88] regarding the ill-posed nature of the structural problem of third-order beams based on the stress-driven nonlocal model.…”
Section: A Nonlocal Methodology For Shear Deformation Beam Theoriesmentioning
confidence: 83%
“…Solutions to the relative elastostatic problem can be found in [87]. It is worth noting that the outcomes contributed in [43] amend the erroneous statements in [88] regarding the ill-posed nature of the structural problem of third-order beams based on the stress-driven nonlocal model.…”
Section: A Nonlocal Methodology For Shear Deformation Beam Theoriesmentioning
confidence: 83%
“…Through Eringen’s nonlocal differential model (ENDM) is extendedly applied to address the size effect of microstructures, inconsistent size-dependent responses are obtained for tensile bar (Benvenuti and Simone, 2013; Pisano and Fuschi, 2003) and flexural beams (Li et al, 2015a; Reddy and Pang, 2008; Zhang et al, 2019a; Zhang and Qing, 2020; Tang and Qing, 2021). In addition, it is also reported that ENDM would lead to ill-posed mathematical formulation for high-order shear deformation beams(Zhang and Qing, 2021b, 2021c; Zhang et al, 2021) and plates(Peddieson et al, 2003; Qing, 2022), since the order of differential governing equations is higher than the number of boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…As another effective strategy, Romano et al (Romano and Barretta, 2017;Romano et al, 2017a) proposed a novel nonlocal constitutive formulation of stressdriven type, which assumes the elastic strain as the integral convolution between the stress field and the nonlocal kernel. Such a strategy also leads to well-posed result for bounded structures, and a consistently stiffening effect can be obtained when increasing nonlocal length-scale parameters (Apuzzo et al, 2017;Barretta et al, 2018b;Barretta et al, 2019b;Pinnola et al, 2020;Russillo et al, 2021;Zhang and Qing, 2021b;Zhang et al, 2020). Subsequently, the stressdriven type two-phase local/nonlocal mixed integral model (Apuzzo et al, 2020;Barretta et al, 2018a) is also formulated by combining the purely stress-driven nonlocal model with the local elasticity theory.…”
Section: Introductionmentioning
confidence: 99%